2019
DOI: 10.1155/2019/8016120
|View full text |Cite
|
Sign up to set email alerts
|

Study on miRNAs in Pan-Cancer of the Digestive Tract Based on the Illumina HiSeq System Data Sequencing

Abstract: Objective. miRNA has gained attention as a therapeutic target in various malignancies. The proposal of this study was to investigate the biological functions of key miRNAs and target genes in cancers of the digestive tract which include esophageal carcinoma (ESCA), gastric adenocarcinoma (GAC), colon adenocarcinoma (COAD), and rectal adenocarcinoma (READ). Materials and Methods. After screening differentially expressed miRNAs (DEMIs) and differentially expressed mRNAs (DEMs) in four digestive cancers from The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…This result was found in various GC cell lines (AGS, MGC-803, and MKN-45) [29]. In rectal adenocarcinoma (READ), Lai CH et al found that the expression of miR-552 in READ tissues (n=162) was much higher than normal tissues (n=3) in TCGA database [30]. By comparing the expression of miR-552 between 51 osteosarcomas (OS) tissues and 19 adjacent normal tissues, it was found that the expression level of miR-552 was significantly increased in OS tissues [6].…”
Section: The Clinical Significance Of Mir-552 In Human Cancermentioning
confidence: 85%
See 1 more Smart Citation
“…This result was found in various GC cell lines (AGS, MGC-803, and MKN-45) [29]. In rectal adenocarcinoma (READ), Lai CH et al found that the expression of miR-552 in READ tissues (n=162) was much higher than normal tissues (n=3) in TCGA database [30]. By comparing the expression of miR-552 between 51 osteosarcomas (OS) tissues and 19 adjacent normal tissues, it was found that the expression level of miR-552 was significantly increased in OS tissues [6].…”
Section: The Clinical Significance Of Mir-552 In Human Cancermentioning
confidence: 85%
“…The expression of miR-552 in HCC is more than twice that of normal tissues [3]. The expression of miR-552 in READ is 3.20 times that of normal tissues [30]. Compared with normal tissues, the expression level of miR-552 in metastatic lung adenocarcinomas is 39 times higher [7].…”
Section: The Clinical Significance Of Mir-552 In Human Cancermentioning
confidence: 99%
“…The combination of miR-133a and FOBT could be a potential detection mode in colorectal cancer screening 83 . Based on the information from The Cancer Genome Atlas (TCGA) database and Meta-analysis results, along with bioinformatics analysis, miR-133a was recognized as a potential biomarker of NSCLC 84 - 86 , oral cancer 87 , 88 , osteosarcoma 89 , cervical cancer 90 , prostate cancer 91 , digestive tumors 92 including EC 93 - 95 , GC 96 , 97 , pancreatic ductal adenocarcinoma (PDAC) 98 and CRC 99 . A study of 8006 tumors including 19 tumor types suggested that hypoxia contributed to genomic instability.…”
Section: Mir-133a As a Potential Biomarkermentioning
confidence: 99%
“…At the same time, accumulating evidence has elucidated that the PI3K–Akt signaling pathway is highly activated ( Guo et al, 2015 ; Hao et al, 2019 ) and is a validated therapeutic target in RCC ( Lin et al, 2014 ). Key miRNAs and target genes have been reported to be mainly related to the PI3K–Akt signaling pathway in GI cancers ( Lai et al, 2019 ). A bioinformatics analysis showed that the DEGs of EC compared with normal tissues are mainly enriched in the PI3K–Akt signaling pathway ( Li M. et al, 2020 ; Yu-Jing et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%